Bioinformatics Analysis of Potential Targets of Betulinic Acid Against Virulence Factors of Chlamydia trachomatis - Nurani, Erla; Roza, Putri Diana; Darmawi, Darmawi; Irham, Lalu Muhammad; Adikusuma, Wirawan; Anggraini, Dewi (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Chlamydia trachomatis is an obligate intracellular pathogen responsible for trachoma and sexually transmitted infections, with rising antibiotic resistance posing a major therapeutic challenge. Natural compounds such as betulinic acid, a pentacyclic triterpenoid with broad-spectrum antimicrobial and anti-inflammatory properties, offer potential as alternative therapeutic agents. This study aimed to analyze the potential targets of betulinic acid against C. trachomatis virulence factors using bioinformatics approaches. Protein–compound interaction prediction was performed using STITCH v5.0, while virulence classification was analyzed through VICMpred and VirulentPred. BepiPred v2.0 was employed to identify B-cell epitopes, and PSORTb v3.0 was used to predict subcellular localization. The results identified five proteins targeted by betulinic acid, including DNA topoisomerase IV subunit B (parE), DNA topoisomerase IV subunit A (parC), DNA gyrase subunits (gyrA and gyrB), and sulfite reductase (cysJ). Among these, three were classified as virulence factors: parE (0,2959), parC (0,1754), and cysJ (0,4018). Subcellular localization analysis showed that parE and parC are cytoplasmic proteins essential for DNA replication, while cysJ is associated with the cytoplasmic membrane and metabolic processes. Betulinic acid showed strong potential as an antimicrobial compound targeting key virulence proteins of C. trachomatis. These findings provide foundational insight for further experimental studies to develop betulinic acid–based therapeutic strategies against chlamydial infections.